Integrating Google Earth in Problem Based Learning to Improve Spatial Thinking Skills of High School Students in Geography Learning - Titi Sari; Mukminan Mukminan (Jurnal Inovasi Pendidikan dan Sains, 2025)
The initial survey showed that high school students had low spatial thinking skills (STS). This quasi-experimental study aimed to examine the effectiveness of Google Earth in enhancing STS, identifying the most developed spatial thinking component, and exploring students’ perceptions of its use in geography learning. The study involved two senior high schools in Central Java, with 36 students in the experimental group and 46 students in the control group selected using Slovin’s formula and purposive sampling. Data were collected through observation, STS tests, and document analysis, and analyzed using Gain Score, Independent Sample t-test, and descriptive analysis. Results showed that Google Earth significantly improved STS. The experimental group’s average score increased from 40.28 (pre-test) to 86.62 (post-test), while the control group improved only from 40.91 to 67.19. The Independent Sample t-test produced a significance value of 0.0001 < 0.05, rejecting H0. Based on gain score criteria, the improvement in the experimental group was categorized as high, while the control group showed a medium improvement. The most developed component was Condition, where students reported that Google Earth’s interactive features enhanced their understanding of geographic situations. In conclusion, Google Earth is effective in improving STS and is recommended for geography learning in senior high schools